(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The Molise and Apulia subsurface exploration has found clastic calcareous layers at the top of the Mesozoic—Miocene carbonate sequence and within the Middle Pliocene turbidites. The first are the result of Karst—fissures and crushing on the structural highs and mass flows at the base of fault slopes. Within the turbidites a biocalcarenitic horizon IS an electric good marker which proves an event of a shelf build up. It corresponds to the Middle Pliocene gap widely developed in the Apennines.